How to prove non-ergodicity of Volterra quadratic stochastic operators: a general strategy - Ganikhodzaev, Rasul; Saburov, Mansoor (2012)
In this paper, we shall give a general program of proving non-ergodicity of Volterra QSO (quadratic stochastic operator). This program already mentioned in the first author's doctor of science thesis. However, there is another program to do so [1]. Here, we are going to provide some examples to support our program. It is worth pointing out that some results of the paper [1] can be derived from our general result.